2020
DOI: 10.1111/jace.17354
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of elastic behavior of alite paste at early hydration stages

Abstract: Elastic behavior is an important aspect of fresh cement‐based materials. In this paper, the elasticity development of fresh pure alite paste within 5 hours was monitored in situ by small amplitude oscillation shear. Isothermal microcalorimetry, X‐ray diffraction, scanning electronic microscopy, 1H nuclear magnetic resonance, zeta potential measurements were used to investigate the underlying mechanisms. It was found that the evolution of storage modulus can be characterized by three different stages. The first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 57 publications
(128 reference statements)
0
7
0
Order By: Relevance
“…Finally, the storage modulus of the mixture demonstrates a continuous increase concurrent with the enlargement of the C–S–H bridges 9,25 . Additionally, recent studies also found that a liner relation between the formation of C–S–H and the increase of storage modulus 27 …”
Section: Resultsmentioning
confidence: 77%
“…Finally, the storage modulus of the mixture demonstrates a continuous increase concurrent with the enlargement of the C–S–H bridges 9,25 . Additionally, recent studies also found that a liner relation between the formation of C–S–H and the increase of storage modulus 27 …”
Section: Resultsmentioning
confidence: 77%
“…28 On the other hand, the G′ of the C 3 S paste increases continuously with time due to the dissolution−precipitation reaction upon contact with water. 51 In the very beginning, the G′ of the paste is linked mainly with the high ion concentration in the pore solution due to the massive dissolution of C 3 S (initial low C−S−H precipitation), resulting in a very cohesive behavior at rest but fragile once sheared (γ ≥ γ cr ). Following the hydration process, the continuous C−S−H particles' precipitation starts to influence the overall contact area, which increases over time (contact aging 61 ) until C−S−H percolation and final rigidification of the paste (setting).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…On the other hand, the G ′ of the C 3 S paste increases continuously with time due to the dissolution–precipitation reaction upon contact with water . In the very beginning, the G ′ of the paste is linked mainly with the high ion concentration in the pore solution due to the massive dissolution of C 3 S (initial low C–S–H precipitation), resulting in a very cohesive behavior at rest but fragile once sheared (γ ≥ γ cr ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The small-amplitude oscillatory shear is commonly used to test the viscoelasticity of pastes, and the applied shear rate varies with time in the form of a sinusoidal function. 47 However, as the shear rate of cement pastes generally increases linearly or logarithmically in most tests (Figure 3A), the rheological parameters are usually measured using a rotational coaxial cylinder.…”
Section: Selection Of Rheological Testing Schemementioning
confidence: 99%